PENGARUH PENERAPAN MODEL PEMBELAJARAN REFLEKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIS MAHASISWA CALON GURU - Rohana Rohana; Yunika Lestaria Ningsih (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis study aims to : 1) find out the enhancement ability of the problem solving and mathematical communication, 2) the interaction between the learning model and the level of the students’ ability toward the enhancement ability of problem solving and mathematical communication. The data were collective through tes and interview. The data were analyzed quantitatively using a t-test and Two Ways Anova. The result show that the enhancement ability of problem solving and mathematical communication of the students’ who acquired the Reflective learning model is bettter than students who received the conventional learning, according to the whole student or students’ ability level. There is no interaction between the learning model and level of students’ ability toward the enhancement ability of problem solving and mathematical communication. Its mean that theenhancement of students ability is affected by the application of the learning model.Keywords: Reflective Learning, problem solving ability, mathematical communication ability